Respuesta :

Answer:

the given expression [tex](6d^2 - 9d- 15)[/tex] is factored as (d+1)(2 d-5)

Step-by-step explanation:

Here, the given expression is:

[tex]6d^2 - 9d- 15= 0[/tex]

Now, simplifying the given expression,we get:

[tex]6d^2 - 9d- 15= 0 \\\implies 3(2d^2 - 3d- 5) = 0\\\implies 2d^2 - 3d- 5 = 0[/tex]

Now, we need to split the middle term -3 in such a way, that on addition it given -3 and on multiplication it given -10.

[tex]2d^2 - 3d- 5 = 0\\\implies 2d^2 + 2d- 5d - 5 = 0\\\implies 2d(d+1) -5(d+1) = 0\\\implies (d+1)(2d-5) = 0[/tex]

So, either(d+1)  = 0 OR (2d-5) = 0

[tex](6d^2 - 9d- 15) = (d+1)(2d-5)[/tex]

Hence the given expression [tex](6d^2 - 9d- 15)[/tex] is factored as (d+1)(2 d-5) =  0